A method for regenerating discarded Teflon high-temperature cloth for latex foam mattresses
Through specific cleaning and coating treatment, the uneven heat transfer and non-stickiness problems of discarded Teflon high-temperature cloth are solved, its separation ability from latex foam mattress is restored, and the regeneration of high adhesion and wear resistance is achieved, making it suitable for latex foam mattresses.
Patent Information
- Application Number
- CN202511067256.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-31
- Publication Date
- 2025-10-03
- Estimated Expiration
- 2045-07-31
AI Technical Summary
Due to coating wear and accumulation of pollutants, discarded Teflon high-temperature cloth leads to uneven heat transfer and reduced non-stickiness, making it difficult to separate from the latex foam mattress, causing product damage, and it is difficult to effectively regenerate it using conventional processes.
Ultrasonic water washing, specific solvent immersion, alkaline solution treatment, coupling agent and phytic acid pretreatment, combined with polyamic acid solution dipping and segmented sintering, are used to form a continuous polyimide membrane, which is then compounded with PFA and PTFE emulsion to form a coating with high adhesion and good wear resistance.
The non-stickiness and mechanical properties of discarded Teflon high-temperature cloth are restored, meeting the application requirements of latex foam mattresses, extending service life and reducing environmental pollution.
Smart Images

Figure CN120556273B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of recycling Teflon high-temperature cloth, in particular to a method for regenerating discarded Teflon high-temperature cloth for latex foam mattresses. Background Art
[0002] Polytetrafluoroethylene glass fiber cloth, also known as Teflon glass fiber cloth, Teflon high-temperature cloth, etc., has the advantages of good corrosion resistance, high temperature resistance, low friction coefficient, extremely low surface energy, and is not easy to adhere to grease, stains or sticky substances. It is widely used in fields with high temperature resistance and high non-stick requirements, such as high-temperature conveyor belts, high-temperature release cloths, etc.
[0003] Latex foam mattresses are porous rubber materials with a cell structure characterized by all or most interconnected pores, with a small number of discontinuous pores. They consume the most latex among latex products and are characterized by high elasticity, shock absorption, compression fatigue resistance, good load-bearing capacity, and comfort and durability, making them increasingly popular. Latex foam mattresses are made from rubber sap collected from rubber trees. Using high-temperature foaming equipment, the latex is processed on a Teflon cloth (conveyor belt) through a series of processes, including demolding, foaming, gelling, vulcanization, washing, drying, molding, demolding, and packaging. The result is a modern, eco-friendly bedroom product with numerous excellent properties, ideal for high-quality, healthy sleep. The high-temperature foaming temperature for latex mattresses generally ranges from 150-180°C. Heat is transferred to the latex liquid layer via the Teflon cloth, causing the foaming process. The non-stick properties of the latex cloth allow for seamless demolding, resulting in a smooth, defect-free surface and a high-quality latex foam mattress. However, with increasing use, the Teflon fabric's surface coating wears away, and small amounts of latex residue accumulate, leading to uneven heat transfer during the subsequent latex foaming process. Furthermore, the smoothness and wear of the Teflon fabric's surface coating make it difficult to separate the latex product from the Teflon fabric, which in turn causes defects such as breakage and tearing during the removal process. At this point, the Teflon fabric becomes discarded and becomes waste. Generally speaking, for latex mattresses thicker than 10mm, the lifespan of a Teflon fabric is 3-4 months. However, thinner latex foam mattresses, 5-10mm thick, have poor tear resistance and require a higher level of non-stickiness. If the Teflon fabric becomes difficult to separate from the latex foam mattress, it cannot be used, otherwise the mattress will tear and become scrapped. Therefore, the lifespan of the Teflon fabric used is generally less than 2 months. This results in a large amount of discarded Teflon fabric within the industry, making it difficult to use, resulting in significant economic losses and environmental pollution.
[0004] However, since these discarded Teflon high-temperature cloth products have wear spots and pollutants on the surface, even after repeated cleaning, they cannot reach the purity of pure glass fiber base cloth. At the same time, the wear points on the coating and the glass fiber base cloth surface cause problems such as decreased tensile properties, easy cracking, insufficient wear resistance, etc. More importantly, the surface of the discarded Teflon high-temperature cloth after cleaning has poor bonding with the low surface tension polytetrafluoroethylene emulsion. Conventional processes such as direct multiple immersion in PTFE emulsion and high-temperature sintering are difficult to effectively adhere to, resulting in not only poor mechanical properties and wear resistance of the Teflon high-temperature cloth, but also easy bubbling at high temperature and easy cracking at the original wear points. It is difficult to achieve effective regeneration of discarded Teflon high-temperature cloth for latex foam mattresses using conventional PTFE emulsion and dip coating and sintering processes. Summary of the Invention
[0005] In order to solve the above problems, the present invention provides a regeneration method for discarded Teflon high-temperature cloth for latex foam mattresses. First, a special cleaning process is performed to clean the latex particles and other impurities remaining on the discarded Teflon high-temperature cloth, providing a good foundation for subsequent dipping. Then, pre-treatment is performed to enhance the surface adhesion. Then, two dip-coating and segmented sintering treatments are performed with a special polyamide acid solution. Subsequently, two different PTFE emulsion combination dip-coatings and high-temperature sintering are performed to form the obtained recycled Teflon high-temperature cloth. Not only is the coating film excellent in non-stickiness, the coating film is complete and smooth, and the mechanical strength is significantly improved. It has excellent adhesion to the discarded Teflon high-temperature cloth substrate, and is resistant to high temperatures and boiling water, and can meet the application requirements of the latex foam mattress industry.
[0006] The purpose of the present invention is to provide a method for regenerating waste Teflon high-temperature cloth used for latex foam mattresses.
[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are adopted:
[0008] The present invention provides a method for regenerating waste Teflon high-temperature cloth for latex foam mattresses, comprising the following steps:
[0009] (1) The discarded Teflon high-temperature cloth is ultrasonically washed to remove dust from the surface, and then dried;
[0010] (2) soaking the Teflon high-temperature cloth dried in step (1) in a solvent at high temperature, wherein the solvent is a mixture of DMF and butyl acetate, and the mass ratio of DMF to butyl acetate is 2:1-1.5; then soaking it in ethanol at room temperature, and hanging it to dry; then soaking the dried Teflon high-temperature cloth in alkali solution at high temperature, wherein the alkali solution is a sodium hydroxide aqueous solution with a concentration of 20-25%; then neutralizing it with acetic acid at room temperature, wherein the concentration of acetic acid is 3-5%; then washing it with tap water at room temperature, and then washing it with deionized water at room temperature, hanging it to dry;
[0011] (3) soaking the Teflon high-temperature cloth dried in step (2) in a pretreatment solution at room temperature, wherein the pretreatment solution is a mixed ethanol solution of a coupling agent and phytic acid, the total mass concentration of the coupling agent and phytic acid in the ethanol solution is 1.5-2%, and the mass ratio of the coupling agent to the phytic acid is 10-12:1;
[0012] (4) The pre-treated Teflon high-temperature cloth is hung up and fully dried, and then soaked in a polyamic acid solution modified by dimethylmethoxychlorosilane grafting at room temperature, hung up to dry, and sintered at high temperature in sections to obtain a Teflon high-temperature cloth after a single dip coating;
[0013] (5) soaking the Teflon high-temperature cloth after the first dip coating in a non-grafted modified polyamic acid solution at room temperature, hanging it to dry, and sintering it at high temperature in sections to obtain the Teflon high-temperature cloth after the second dip coating;
[0014] (6) The Teflon high-temperature cloth after the second dip coating is immersed in the first mixed emulsion at room temperature, hung to dry, first heated to 260-270 ° C and dried for 2-2.5 minutes, and then sintered at 360-365 ° C for 1.5-2 minutes to obtain the Teflon high-temperature cloth after the third dip coating; the first mixed emulsion is a mixture of PFA emulsion, first PTFE emulsion and water, the mass ratio of PFA emulsion to first PTFE emulsion is 1:0.8-1.2, and the total solid content of the first mixed emulsion is 30-35%; the first PTFE emulsion is JF-4DCD emulsion;
[0015] (7) The Teflon high-temperature cloth after three dip coatings is immersed in the second mixed emulsion at room temperature, hung to dry, first heated to 260-270 ° C and dried for 2-2.5 minutes, and then sintered at 370-375 ° C for 2.5-3 minutes to obtain the Teflon high-temperature cloth after four dip coatings; the second mixed emulsion is a mixture of the second PTFE emulsion, the third PTFE emulsion and water, the mass ratio of the second PTFE emulsion to the third PTFE emulsion is 1:2-2.5, and the total solid content of the second mixed emulsion is 45-50%; the second PTFE emulsion is JF-4DCF emulsion, and the third PTFE emulsion is JF-4DCT emulsion.
[0016] When manufacturing latex foam mattresses, the non-stick properties of Teflon high-temperature cloth (conveyor belt) are typically used to carry out processes such as latex demolding, foaming, gelling, vulcanization, water washing, and drying. After forming, the fabric is peeled off. Due to repeated use, raw materials and impurities easily adhere to the Teflon high-temperature cloth, affecting the smoothness of the coating. This makes it difficult to de-mold the latex product from the Teflon high-temperature cloth, resulting in breakage and tearing, and its non-stick properties cannot be fully utilized, resulting in replacement after only one to two months of use. Furthermore, wear points not only lead to a decrease in mechanical properties, but also poor surface adhesion, making conventional processes difficult to adhere to and difficult to regenerate. The present invention can achieve regeneration and restore its original properties, especially for the high requirements for non-stick properties, and the adhesion and mechanical properties are not much different from those of new Teflon high-temperature cloth.
[0017] The discarded Teflon high-temperature cloth of the present invention refers to the Teflon high-temperature cloth whose coating is contaminated, smoothness is reduced, and non-stickiness can no longer meet the requirements (for example, the non-stickiness is reduced from the original level I to level III) after repeated use.
[0018] Preferably, the thickness of the discarded Teflon high-temperature cloth is 0.5 mm, and the original product comes from Yangzhou Jiachuang Latex Products Co., Ltd.
[0019] Preferably, in step (1), the ultrasonic washing time is 2-3 minutes.
[0020] Preferably, in step (2), the solvent soaking temperature is 70-80°C, the soaking time is 4-5 minutes; the ethanol soaking time is 30-60 seconds; the alkali solution soaking temperature is 50-60°C, the soaking time is 2-3 minutes; the acetic acid neutralization time is 10-20 seconds;
[0021] Preferably, in step (2), the tap water rinsing time is 30-60 seconds, the deionized water rinsing time is 1-2 minutes; the drying temperature is 130-140°C, and the drying time is 3-4 minutes.
[0022] Preferably, in step (3), the pretreatment liquid immersion time is 40-60s;
[0023] The mixed ethanol solution of coupling agent and phytic acid is a solution prepared by coupling agent, phytic acid and ethanol;
[0024] Preferably, in step (3), the coupling agent is γ-aminopropylmethyldiethoxysilane or 3-aminopropyltrimethoxysilane.
[0025] Preferably, in step (4), the soaking time is 40-50s;
[0026] Preferably, in step (4), the segmented high-temperature sintering includes: 130°C / 10 min, 200°C / 10 min, 320°C / 5 min, and 350°C / 5 min.
[0027] The continuous polyimide film is obtained through immersion treatment with polyamic acid solution and segmented high-temperature sintering process. It can effectively repair the defects of the original high-temperature cloth caused by wear, such as insufficient wear resistance, easy cracking, and decreased mechanical strength. It can also enhance the wear resistance of the bottom layer of the high-temperature cloth and the strength of the high-temperature cloth, improve the tensile strength and wear resistance of the high-temperature cloth in subsequent use, and achieve the purpose of protecting the base glass fiber cloth.
[0028] Preferably, in step (4), the preparation of the polyamic acid solution grafted with dimethylmethoxysilyl chloride comprises the following steps:
[0029] (a) adding anhydrous N,N-dimethylacetamide and 1,3-bis(4'-aminophenoxy)benzene to a reaction kettle, controlling the temperature to 15-20°C, stirring and dissolving, then adding a mixture of pyromellitic dianhydride and hexafluorodianhydride in 3-4 batches, with an interval of 35-40 minutes between each batch. After all the additions are completed, stirring is continued for 10-15 hours. The solid content of the polyamic acid solution is adjusted to 20-22% by adjusting the amount of anhydrous N,N-dimethylacetamide. The reaction is continued until the viscosity of the solution reaches 3000-3500 mPa.s, thereby obtaining an ungrafted polyamic acid solution;
[0030] The molar ratio of the raw materials is: 10-13 parts of 1,3-bis(4'-aminophenoxy)benzene, 6-8 parts of pyromellitic dianhydride, and 3-4 parts of hexafluorodianhydride;
[0031] (b) adding dimethylmethoxychlorosilane to the ungrafted polyamic acid solution obtained in step (a) to carry out a grafting modification reaction, wherein the mass ratio of the polyamic acid solution to the dimethylmethoxychlorosilane is 100:0.5-0.6, sampling is performed for gas chromatography detection, and when the conversion rate of the dimethylmethoxychlorosilane reaches more than 98%, the reaction is stopped, and anhydrous N,N-dimethylacetamide is added as a solvent to adjust the solid content to 15-16%, thereby obtaining a polyamic acid solution grafted with dimethylmethoxychlorosilane.
[0032] The anhydrous N,N-dimethylacetamide is prepared by using industrial-grade N,N-dimethylacetamide and anhydrous sodium sulfate in a mass ratio of 10:0.2-0.3, stirring at room temperature for 20-30 minutes, removing water again, and filtering to obtain the product, with a moisture content of less than 0.3%.
[0033] The polyamic acid solution used in the present invention adopts a specific raw material combination. The prepared polyamic acid solution has more polar groups in the chain segments, and its own adhesion to the glass fiber base cloth is better. Moreover, the polyamic acid solution after dimethylmethoxychlorosilane grafting modification has better bonding strength with the glass fiber base cloth than polytetrafluoroethylene with low surface tension. During the regeneration and coating process of discarded Teflon high-temperature cloth, it can improve the adhesion and wetting ability with the cleaned high-temperature cloth, thereby avoiding defects such as bubbling and cracking of the coating during subsequent use.
[0034] Preferably, in step (5), the soaking time is 40-50s;
[0035] Preferably, in step (5), the segmented high-temperature sintering includes: 150°C / 10 min, 250°C / 10 min, 330°C / 5 min, and 360°C / 5 min.
[0036] Preferably, in step (5), the preparation of the ungrafted polyamic acid solution comprises the following steps:
[0037] Add anhydrous N,N-dimethylacetamide and 1,3-bis(4'-aminophenoxy)benzene to a reaction kettle, control the temperature to 15-20° C., stir and dissolve, then add a mixture of pyromellitic dianhydride and hexafluorodianhydride in 3-4 batches, with an interval of 35-40 minutes between each batch. After all the additions are completed, continue stirring for 10-15 hours, adjust the solid content of the polyamic acid solution to 20-22% by adjusting the amount of anhydrous N,N-dimethylacetamide, and continue the reaction until the viscosity of the solution reaches 3000-3500 mPa.s to obtain an ungrafted polyamic acid solution;
[0038] The molar ratio of the raw materials is: 10-13 parts of 1,3-bis(4'-aminophenoxy)benzene, 6-8 parts of pyromellitic dianhydride, and 3-4 parts of hexafluorodianhydride.
[0039] Preferably, in step (6), the soaking time is 30-40 seconds.
[0040] Preferably, in step (7), the soaking time is 30-40s.
[0041] PFA emulsion can be the model AD-2CRER product of Japan Daikin Company;
[0042] JF-4DCD emulsion, JF-4DCF emulsion and JF-4DCT emulsion are all products of Juhua Company.
[0043] Technical effects:
[0044] The present invention is subjected to a high-temperature soaking and washing treatment with a specific solvent, and then to a high-temperature alkali soaking and washing treatment, so as to clean the impurities such as latex particles remaining on the discarded Teflon high-temperature cloth as much as possible, thereby providing a good foundation for subsequent dip coating, and then a specific coupling agent and phytic acid are used for pre-treatment to enhance the surface adhesion, and then the prepared grafted modified polyamic acid solution is used for a first dip coating and segmented imidization sintering to obtain a primer with excellent adhesion and significantly improved strength, and then a non-grafted modified polyamic acid solution is used for a second dip coating on the basis of the primer, and a dense, high-strength The polyimide coating with excellent strength and wear resistance is obtained by twice soaking treatment in different polyamic acid solutions and segmented high-temperature sintering process to obtain a continuous polyimide film. Due to its relatively strong polarity and functional group modification, it has a high bonding force with the substrate, which not only significantly improves the adhesion to the Teflon high-temperature cloth substrate, but also can effectively repair the defects of insufficient wear resistance, easy cracking, and decreased mechanical strength caused by the wear of the original high-temperature cloth. It can also enhance the wear resistance of the bottom layer of the high-temperature cloth and the strength of the high-temperature cloth, improve the tensile strength and wear resistance of the high-temperature cloth in subsequent use, and achieve the purpose of protecting the substrate glass fiber cloth. Moreover, the formation of the polyimide coating is also conducive to the connection of subsequent PFA emulsion and PTFE emulsion, and then through the compounding of PFA emulsion and low-viscosity PTFE emulsion (JF-4DCD emulsion), it is connected with the polyimide layer to form an intermediate layer with good bonding force. Finally, high-gloss, non-stick PTFE emulsion (JF-4DCF emulsion) and PTFE emulsion (JF-4DCT emulsion) are used for surface dip coating and high-temperature sintering to obtain the fourth layer of coating on the surface. Finally, the non-stick Teflon coating is excellent, and the coating is complete and smooth. The recycled product can meet the application requirements of the latex foam mattress industry. The new Teflon high-temperature cloth obtained can continue to be used in the foam latex industry, and its performance is not much different from that of the new Teflon high-temperature cloth.
[0045] The present invention has been described in detail above, but the above embodiments are merely illustrative in nature and are not intended to limit the present invention. In addition, the present invention is not limited by any theory described in the above prior art or invention summary or the following examples. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 This is a picture of the surface of discarded Teflon high-temperature cloth before recycling (magnified 200 times);
[0047] Figure 2 This is a picture of the surface of discarded Teflon high-temperature cloth after recycling (magnified 200 times). DETAILED DESCRIPTION
[0048] The present invention will be further described below with reference to the examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed in the present invention.
[0049] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, and methods in the art.
[0050] raw material:
[0051] The discarded Teflon high-temperature cloth comes from the 7-10mm latex foam product production line of Yangzhou Jiachuang Latex Products Co., Ltd., which was used for about 1.8 months (54 days). The new cloth comes from Huangshan Meiao Composite Materials Co., Ltd., model 1060JK, with a thickness of 0.5mm and a weight of 1022g / m 2 );
[0052] The PFA emulsion is the AD-2CRER product of Japan Daikin Company, with a solid content of 50%;
[0053] The JF-4DCD emulsion is a model JF-4DCD product of Juhua Group Co., Ltd., with a solid content of 60%.
[0054] JF-4DCF emulsion is a product of Juhua Group Co., Ltd., model JF-4DCF, with a solid content of 60.2%;
[0055] JF-4DCT emulsion is a model JF-4DCT product of Juhua Group Co., Ltd., with a solid content of 61%.
[0056] Preparation Example Preparation of dimethylmethoxychlorosilane grafted polyamic acid solution:
[0057] (a) adding an appropriate amount of anhydrous N,N-dimethylacetamide and 12 molar parts of 1,3-bis(4'-aminophenoxy)benzene to a reaction kettle, controlling the temperature to 15-20°C, stirring and dissolving, then adding a mixture of 7 molar parts of pyromellitic dianhydride and 4 molar parts of hexafluorodianhydride in 3-4 batches, with an interval of 35-40 minutes between each batch. After all the additions are completed, stirring is continued for 10-15 hours, and the solid content of the polyamic acid solution is adjusted to 21% by adjusting the amount of anhydrous N,N-dimethylacetamide. The reaction is continued until the viscosity of the solution reaches 3000-3500 mPa.s to obtain an ungrafted polyamic acid solution;
[0058] (b) adding dimethylmethoxychlorosilane to the ungrafted polyamic acid solution for grafting modification reaction, wherein the mass ratio of the polyamic acid solution to the dimethylmethoxychlorosilane is 100:0.5, sampling is performed for gas chromatography detection, and when the conversion rate of the dimethylmethoxychlorosilane reaches more than 98%, the reaction is stopped, and anhydrous N,N-dimethylacetamide is added as a solvent to adjust the solid content to 15%, thereby obtaining a polyamic acid solution grafted with dimethylmethoxychlorosilane.
[0059] Example 1
[0060] A method for regenerating discarded Teflon high-temperature cloth for latex foam mattresses comprises the following steps:
[0061] (1) Discarded Teflon high temperature cloth (before regeneration, Figure 1 The surface was cleaned by ultrasonic water washing for 2 minutes and then dried with hot air;
[0062] (2) Soaking the Teflon high-temperature cloth dried in step (1) in a solvent at a high temperature of 70°C for 5 minutes, wherein the solvent is a mixture of DMF and butyl acetate, and the mass ratio of DMF to butyl acetate is 2:1; soaking it in ethanol at room temperature for 50 seconds, and hanging it to dry; then soaking the dried Teflon high-temperature cloth in alkali solution at a high temperature of 55°C for 2 minutes, wherein the alkali solution is a 20% sodium hydroxide aqueous solution; neutralizing it with acetic acid at room temperature for 15 seconds, wherein the acetic acid concentration is 4%; then washing it with tap water at room temperature for 30 seconds, and then washing it with deionized water at room temperature for 2 minutes, hanging it up, and drying it with hot air at 135°C for 4 minutes;
[0063] (3) The Teflon high-temperature cloth dried in step (2) was pre-treated by soaking in a pre-treatment solution at room temperature for 50 seconds. The pre-treatment solution was a mixed ethanol solution of a coupling agent and phytic acid. The total mass concentration of the coupling agent and phytic acid in the ethanol solution was 2%, and the mass ratio of the coupling agent to the phytic acid was 10:1. The coupling agent was γ-aminopropylmethyldiethoxysilane.
[0064] (4) The Teflon high-temperature cloth after pretreatment is hung up and placed in a 220°C drying tunnel for 2 minutes. After being fully dried, it is immersed in the polyamic acid solution modified by dimethylmethoxychlorosilane obtained in the preparation example at room temperature for 40 seconds, hung up to dry, and sintered at high temperature in sections of 130°C / 10 minutes + 200°C / 10 minutes + 320°C / 5 minutes + 350°C / 5 minutes to obtain the Teflon high-temperature cloth after one-time dip coating;
[0065] (5) Soaking the Teflon high-temperature cloth after the primary dip coating in the ungrafted modified polyamic acid solution obtained in step (a) of the preparation example at room temperature for 40 seconds, hanging it to dry, and sintering it at high temperature in sections of 150°C / 10min+250°C / 10min+330°C / 5min+360°C / 5min to obtain the Teflon high-temperature cloth after the secondary dip coating;
[0066] (6) The Teflon high-temperature cloth after the second dip coating was soaked in the first mixed emulsion at room temperature for 35 seconds, hung to dry, first heated to 260°C and dried for 2.5 minutes, and then sintered at 360°C for 2 minutes to obtain the Teflon high-temperature cloth after the third dip coating; the first mixed emulsion was a mixture of PFA emulsion, a first PTFE emulsion (JF-4DCD emulsion) and water, the mass ratio of PFA emulsion to JF-4DCD emulsion was 1:1, and the total solid content of the first mixed emulsion was 30%;
[0067] (7) The Teflon high-temperature cloth after three dip coatings was soaked in the second mixed emulsion at room temperature for 35 seconds, hung to dry, first heated to 260 ° C and dried for 2.5 minutes, and then sintered at 370 ° C for 3 minutes to obtain the Teflon high-temperature cloth after four dip coatings (i.e., the regenerated Teflon high-temperature cloth, such as Figure 2 The second mixed emulsion is a mixture of a second PTFE emulsion (JF-4DCF emulsion), a third PTFE emulsion (JF-4DCT emulsion) and water, the mass ratio of JF-4DCF emulsion to JF-4DCT emulsion is 1:2, and the total solid content of the second mixed emulsion is 45%.
[0068] Example 2
[0069] A method for regenerating discarded Teflon high-temperature cloth for latex foam mattresses comprises the following steps:
[0070] (1) The discarded Teflon high-temperature cloth was ultrasonically washed for 2 minutes to remove dust from the surface, and then dried with hot air;
[0071] (2) Soaking the Teflon high-temperature cloth dried in step (1) in a solvent at a high temperature of 80°C for 4 minutes, wherein the solvent is a mixture of DMF and butyl acetate, and the mass ratio of DMF to butyl acetate is 2:1.5; soaking it in ethanol at room temperature for 40 seconds, and hanging it to dry; then soaking the dried Teflon high-temperature cloth in alkali solution at a high temperature of 50°C for 3 minutes, wherein the alkali solution is a 22% sodium hydroxide aqueous solution; neutralizing it with acetic acid at room temperature for 10 seconds, wherein the acetic acid concentration is 5%; then washing it with tap water at room temperature for 40 seconds, and then washing it with deionized water at room temperature for 1 minute, hanging it up, and drying it with hot air at 135°C for 3 minutes;
[0072] (3) The Teflon high-temperature cloth dried in step (2) was pre-treated by soaking in a pre-treatment solution at room temperature for 40 seconds. The pre-treatment solution was a mixed ethanol solution of a coupling agent and phytic acid. The total mass concentration of the coupling agent and phytic acid in the ethanol solution was 1.5%, and the mass ratio of the coupling agent to the phytic acid was 11:1. The coupling agent was γ-aminopropylmethyldiethoxysilane.
[0073] (4) The Teflon high temperature cloth after pre-treatment is hung and put into the 220℃ drying tunnel for 2 minutes. After being fully dried,
[0074] The polyamic acid solution modified by dimethylmethoxychlorosilane grafting obtained in the preparation example was soaked at room temperature for 50 seconds, hung to dry, and sintered at high temperature in stages of 130°C / 10 minutes + 200°C / 10 minutes + 320°C / 5 minutes + 350°C / 5 minutes to obtain a Teflon high-temperature cloth after a single dip coating;
[0075] (5) Soaking the Teflon high-temperature cloth after the primary dip coating in the ungrafted modified polyamic acid solution obtained in step (a) of the preparation example at room temperature for 50 seconds, hanging it to dry, and sintering it at a high temperature of 150°C / 10min+250°C / 10min+330°C / 5min+360°C / 5min in sections to obtain the Teflon high-temperature cloth after the secondary dip coating;
[0076] (6) The Teflon high-temperature cloth after the second dip coating was soaked in the first mixed emulsion at room temperature for 30 seconds, hung to dry, first heated to 265°C and dried for 2 minutes, and then sintered at 365°C for 1.5 minutes to obtain the Teflon high-temperature cloth after the third dip coating; the first mixed emulsion was a mixture of PFA emulsion, a first PTFE emulsion (JF-4DCD emulsion) and water, the mass ratio of PFA emulsion to JF-4DCD emulsion was 1:1, and the total solid content of the first mixed emulsion was 35%;
[0077] (7) The Teflon high-temperature cloth after three dip coatings was soaked in the second mixed emulsion at room temperature for 30 seconds, hung to dry, first heated to 265 ° C and dried for 2 minutes, and then sintered at 375 ° C for 2.5 minutes to obtain the Teflon high-temperature cloth after four dip coatings (i.e., the regenerated Teflon high-temperature cloth); the second mixed emulsion was a mixture of the second PTFE emulsion (JF-4DCF emulsion), the third PTFE emulsion (JF-4DCT emulsion) and water, the mass ratio of JF-4DCF emulsion to JF-4DCT emulsion was 1:2, and the total solid content of the second mixed emulsion was 50%.
[0078] Example 3
[0079] A method for regenerating discarded Teflon high-temperature cloth for latex foam mattresses comprises the following steps:
[0080] (1) The discarded Teflon high-temperature cloth was ultrasonically washed for 2 minutes to remove dust from the surface, and then dried with hot air;
[0081] (2) Soaking the Teflon high-temperature cloth dried in step (1) in a solvent at a high temperature of 75°C for 5 minutes, wherein the solvent is a mixture of DMF and butyl acetate, and the mass ratio of DMF to butyl acetate is 2:1.5; then soaking it in ethanol at room temperature for 60 seconds, hanging it up to dry; then soaking the dried Teflon high-temperature cloth in alkali solution at a high temperature of 60°C for 2 minutes, wherein the alkali solution is a 25% sodium hydroxide aqueous solution; then neutralizing it with acetic acid at room temperature for 10 seconds, wherein the acetic acid concentration is 4%; then washing it with tap water at room temperature for 50 seconds, then washing it with deionized water at room temperature for 1 minute, hanging it up, and drying it with hot air at 140°C for 3 minutes;
[0082] (3) The Teflon high-temperature cloth dried in step (2) was pre-treated by soaking in a pre-treatment solution at room temperature for 60 seconds. The pre-treatment solution was a mixed ethanol solution of a coupling agent and phytic acid. The total mass concentration of the coupling agent and phytic acid in the ethanol solution was 2%, and the mass ratio of the coupling agent to the phytic acid was 12:1. The coupling agent was 3-aminopropyltrimethoxysilane.
[0083] (4) The Teflon high-temperature cloth after pretreatment is hung up and placed in a 220°C drying tunnel for 3 minutes. After being fully dried, it is immersed in the polyamic acid solution modified by dimethylmethoxychlorosilane obtained in the preparation example at room temperature for 45 seconds, hung up to dry, and sintered at high temperature in sections of 130°C / 10 minutes + 200°C / 10 minutes + 320°C / 5 minutes + 350°C / 5 minutes to obtain the Teflon high-temperature cloth after one-time dip coating;
[0084] (5) Soaking the Teflon high-temperature cloth after the primary dip coating in the ungrafted modified polyamic acid solution obtained in step (a) of the preparation example at room temperature for 45 seconds, hanging it to dry, and sintering it at high temperature in sections of 150°C / 10min+250°C / 10min+330°C / 5min+360°C / 5min to obtain the Teflon high-temperature cloth after the secondary dip coating;
[0085] (6) The Teflon high-temperature cloth after the second dip coating was soaked in the first mixed emulsion at room temperature for 40 seconds, hung to dry, first heated to 265°C and dried for 2 minutes, and then sintered at 360°C for 2 minutes to obtain the Teflon high-temperature cloth after the third dip coating; the first mixed emulsion was a mixture of PFA emulsion, a first PTFE emulsion (JF-4DCD emulsion) and water, the mass ratio of PFA emulsion to JF-4DCD emulsion was 1:0.8, and the total solid content of the first mixed emulsion was 30%;
[0086] (7) The Teflon high-temperature cloth after three dip coating was soaked in the second mixed emulsion at room temperature for 40 seconds, hung to dry, first heated to 265 ° C and dried for 2.5 minutes, and then sintered at 375 ° C for 2.5 minutes to obtain the Teflon high-temperature cloth after four dip coating (i.e., the regenerated Teflon high-temperature cloth); the second mixed emulsion is a mixture of the second PTFE emulsion (JF-4DCF emulsion), the third PTFE emulsion (JF-4DCT emulsion) and water, the mass ratio of JF-4DCF emulsion to JF-4DCT emulsion is 1:2.5, and the total solid content of the second mixed emulsion is 50%.
[0087] Example 4
[0088] A method for regenerating discarded Teflon high-temperature cloth for latex foam mattresses comprises the following steps:
[0089] (1) The discarded Teflon high-temperature cloth was ultrasonically washed for 2 minutes to remove dust from the surface, and then dried with hot air;
[0090] (2) Soaking the Teflon high-temperature cloth dried in step (1) in a solvent at a high temperature of 75°C for 4 minutes, wherein the solvent is a mixture of DMF and butyl acetate, and the mass ratio of DMF to butyl acetate is 2:1; soaking it in ethanol at room temperature for 30 seconds, and hanging it to dry; then soaking the dried Teflon high-temperature cloth in alkali solution at a high temperature of 55°C for 2 minutes, wherein the alkali solution is a 20% sodium hydroxide aqueous solution; neutralizing it with acetic acid at room temperature for 15 seconds, wherein the acetic acid concentration is 5%; then washing it with tap water at room temperature for 60 seconds, and then washing it with deionized water at room temperature for 1 minute, hanging it up, and drying it with hot air at 130°C for 4 minutes;
[0091] (3) The Teflon high-temperature cloth dried in step (2) was pre-treated by soaking in a pre-treatment solution at room temperature for 50 seconds. The pre-treatment solution was a mixed ethanol solution of a coupling agent and phytic acid. The total mass concentration of the coupling agent and phytic acid in the ethanol solution was 1.5%, and the mass ratio of the coupling agent to the phytic acid was 10:1. The coupling agent was 3-aminopropyltrimethoxysilane.
[0092] (4) The Teflon high-temperature cloth after pretreatment is hung up and placed in a 220°C drying tunnel for 3 minutes. After being fully dried, it is immersed in the polyamic acid solution modified by dimethylmethoxychlorosilane obtained in the preparation example at room temperature for 45 seconds, hung up to dry, and sintered at high temperature in sections of 130°C / 10 minutes + 200°C / 10 minutes + 320°C / 5 minutes + 350°C / 5 minutes to obtain the Teflon high-temperature cloth after one-time dip coating;
[0093] (5) Soaking the Teflon high-temperature cloth after the primary dip coating in the ungrafted modified polyamic acid solution obtained in step (a) of the preparation example at room temperature for 45 seconds, hanging it to dry, and sintering it at high temperature in sections of 150°C / 10min+250°C / 10min+330°C / 5min+360°C / 5min to obtain the Teflon high-temperature cloth after the secondary dip coating;
[0094] (6) The Teflon high-temperature cloth after the second dip coating was soaked in the first mixed emulsion at room temperature for 35 seconds, hung to dry, first heated to 270°C and dried for 2.5 minutes, and then sintered at 365°C for 1.5 minutes to obtain the Teflon high-temperature cloth after the third dip coating; the first mixed emulsion was a mixture of PFA emulsion, a first PTFE emulsion (JF-4DCD emulsion) and water, the mass ratio of PFA emulsion to JF-4DCD emulsion was 1:1.2, and the total solid content of the first mixed emulsion was 35%;
[0095] (7) The Teflon high-temperature cloth after three dip coating was soaked in the second mixed emulsion at room temperature for 35 seconds, hung to dry, first heated to 270 ° C and dried for 2 minutes, and then sintered at 370 ° C for 3 minutes to obtain the Teflon high-temperature cloth after four dip coating (i.e., the regenerated Teflon high-temperature cloth); the second mixed emulsion is a mixture of the second PTFE emulsion (JF-4DCF emulsion), the third PTFE emulsion (JF-4DCT emulsion) and water, the mass ratio of JF-4DCF emulsion to JF-4DCT emulsion is 1:2, and the total solid content of the second mixed emulsion is 48%.
[0096] Comparative Example 1
[0097] The product obtained by using the discarded Teflon high-temperature cloth used in the present invention and only ultrasonically washing and dust removal and drying is used as comparative example 1.
[0098] Comparative Example 2
[0099] A new product of the same commercially available Teflon high-temperature cloth (unused) was purchased from Huangshan Meao Composite Materials Co., Ltd., model 1060JK.
[0100] Comparative Example 3
[0101] The difference from Example 1 is that the solvent in step (2) is replaced by DMF.
[0102] Comparative Example 4
[0103] The difference from Example 1 is that the pretreatment liquid in step (3) is an ethanol solution of the coupling agent with the same concentration.
[0104] Comparative Example 5
[0105] The difference from Example 1 is that the polyamic acid solution grafted and modified with dimethylmethoxychlorosilane is not used as the primer, and the polyamic acid solution that is not grafted and modified is directly used for dip coating (ie, step (4) is not included).
[0106] Comparative Example 6
[0107] The difference from Example 1 is that only the polyamic acid solution grafted and modified by dimethylmethoxychlorosilane is used as the primer, and the ungrafted polyamic acid solution is not used for the secondary dip coating. The secondary dip coating using the ungrafted polyamic acid solution is replaced by a PFA emulsion of the same mass concentration (i.e., the ungrafted polyamic acid solution in step (5) is replaced by a PFA emulsion of the same mass concentration).
[0108] Comparative Example 7
[0109] The difference from Example 1 is that the polyamic acid solution is not used for the first two dip-coatings. The first two dip-coatings use PFA emulsion and PTFE emulsion of the same mass concentration instead of the polyamic acid solution (i.e., the polyamic acid solution modified by dimethylmethoxychlorosilane grafting in step (4) is replaced by PFA emulsion of the same mass concentration, and the polyamic acid solution not grafted and modified in step (5) is replaced by JF-4DCD emulsion of the same mass concentration).
[0110] Test method:
[0111] The solid content test was carried out according to the method in Section 6.3 of GB / T 8298-2017 “Determination of total solid content of latex”, and the test conditions were 130℃ / 40min.
[0112] The tensile strength at break, temperature resistance (high temperature 250℃ / 24h + low temperature -40℃ / 6h), and self-cleaning performance tests were carried out in accordance with JC / T 171.2-2019 "Coated glass fiber cloth Part 2: Polytetrafluoroethylene emulsion coated glass fiber cloth".
[0113] The surface non-stick test is conducted according to method 4.2.2 in GB / T 32095.2-2015 "Performance and Test Specifications for Non-stick Surfaces of Metal Cooking Utensils for Household Food - Part 2: Test Specifications for Non-stick and Abrasion Resistance." The high-temperature cloth to be tested is cut and evenly spread on the bottom of the pot for non-stick testing. The non-stick performance level is Level I > Level II > Level III.
[0114] The results are shown in Table 1.
[0115] Table 1 Comparison of conventional performance of products of Examples and Comparative Examples
[0116]
[0117] Table 2 Comparison of surface application performance of products in Examples and Comparative Examples
[0118]
[0119] As shown in Tables 1 and 2, the products of the present invention (Examples 1-4) utilize a specific regeneration process, pretreatment, and emulsion regeneration formula to recycle discarded Teflon high-temperature fabrics from the latex foam mattress industry. The Teflon high-temperature fabrics produced by this regeneration method exhibit a smooth surface, free of bubbles and wear spots. Their tensile strength at break is comparable to that of commercially available Teflon high-temperature fabrics. In terms of heat resistance, after baking at 250°C for 24 hours and then cooling at -40°C for 6 hours, both tensile strength at break and sealing properties meet application requirements. Regarding self-cleaning performance, the new (regenerated) product achieved a self-cleaning rating of 99.6% or higher, with minimal change after heat treatment. In terms of non-stick performance, both the new product and the product after heat treatment achieved Class I, and the coating showed no change after boiling in boiling water for 10 hours. This demonstrates that the regenerated Teflon high-temperature fabrics of the present invention exhibit excellent overall performance and surface coating properties, meeting the requirements for post-regeneration applications.
[0120] Comparative Example 1 uses the discarded Teflon high-temperature cloth used in the present invention, and only undergoes ultrasonic water washing to remove dust and drying treatment. Its surface is rough and has obvious wear points. Due to the incomplete Teflon coating, its tensile breaking strength is lower than that of the product of the present invention. In terms of its temperature resistance, after high and low temperature treatment, there are obvious bubbles on the surface, and due to the cracks and wear points on the surface, the sealing performance does not meet the requirements. At the same time, the wear and roughness of the coating lead to poor self-cleaning performance, and the non-stick performance only reaches level III. After boiling in boiling water for 10 hours, water stains are immersed in the wear points on the surface, resulting in obvious bubbles and other defects, which cannot meet the application requirements of latex foam mattresses.
[0121] Comparative Example 2 is a new Teflon high-temperature cloth of the same type. Compared with the recycled Teflon high-temperature cloth product of the present invention, its tensile breaking strength is slightly higher than that of the product of the present invention, and other performances are not much different from those of the product of the present invention;
[0122] Comparative Examples 3 and 4 respectively change the types of cleaning solvents and pretreatment liquids. Comparative Example 3 only uses a single solvent DMF due to its single polarity, which makes it difficult to completely remove a very small amount of stains, reducing the bonding strength between the one-time dip coating and the substrate. In Comparative Example 4, phytic acid is not used, and only a coupling agent is used, which makes it difficult to form a stable pretreatment film on the surface of the discarded Teflon high-temperature cloth. The final result is that the overall appearance of the new products of Comparative Examples 3 and 4 is good, but after high and low temperature resistance treatment, the defect in the primer bonding strength causes very slight bubbling on the surface, and the boiling water (10h) performance is also reduced, which will affect the self-cleaning performance and non-stick performance of the coating surface in subsequent applications.
[0123] Comparative Example 5 does not use the polyamic acid solution modified by dimethylmethoxychlorosilane grafting as the primer, and directly uses the unmodified polyamic acid solution for dip coating. Compared with Example 1, this is equivalent to missing a primer with excellent adhesion to the substrate. As a result, not only is the adhesion between the coating and the substrate reduced, but the mechanical strength of the prepared high-temperature cloth is significantly reduced. After the high and low temperature test treatment or the boiling water test, the surface shows slight bubbling. The self-cleaning performance and non-stick performance of the coating film after high and low temperature treatment are also reduced.
[0124] Comparative Example 6 replaces the polyimide coating of the second dip coating with a PFA coating. This results in deficiencies in mechanical properties and coating connection, a decrease in mechanical properties, very slight bubbling on the surface after high and low temperature resistance testing, and a slight decrease in self-cleaning performance.
[0125] Comparative Example 7 replaces the first two polyimide coatings of the present invention with PFA and PTFE coatings respectively. As a result, due to the poor bonding strength of the base layer, slight unevenness and bubbling appear on the surface of the new product, and the mechanical properties are significantly reduced. After high and low temperature resistance test treatment, obvious bubbling appears on the surface, and the sealing performance does not meet the requirements. The self-cleaning performance and non-stick performance are significantly reduced. After boiling in boiling water (10 hours), obvious bubbling appears on the surface, and a small amount of water stains are immersed, indicating that the bonding strength and density of the coating are poor.
[0126] The above results also show that the product obtained by the coordinated regeneration of various processes of the present invention basically meets the application requirements of the latex foam mattress industry. The present invention realizes the regeneration of waste Teflon high-temperature cloth in the latex foam mattress industry, and has obvious economic and environmental value.
[0127] The above embodiments are intended only to illustrate the technical solutions of the present invention and are not intended to limit the same. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced with equivalents, without departing from the spirit and substance of the claims of the present invention; and such modifications or replacements remain within the scope of the claims of the present invention.
Claims
1. A method for regenerating waste Teflon high-temperature cloth for latex foam mattresses, characterized in that: The following steps are involved: (1) The discarded Teflon high-temperature cloth is ultrasonically washed to remove dust from the surface, and then dried; (2) soaking the Teflon high-temperature cloth dried in step (1) in a solvent at a temperature of 70-80°C, wherein the solvent is a mixture of DMF and butyl acetate, and the mass ratio of DMF to butyl acetate is 2:1-1.5; then soaking it in ethanol at room temperature, hanging it to dry; then soaking the dried Teflon high-temperature cloth in an alkali solution at a temperature of 50-60°C, wherein the alkali solution is a sodium hydroxide aqueous solution with a concentration of 20-25%; then neutralizing it with acetic acid at room temperature, wherein the concentration of acetic acid is 3-5%; then washing it with tap water at room temperature, then washing it with deionized water at room temperature, hanging it to dry; (3) soaking the Teflon high-temperature cloth dried in step (2) in a pretreatment solution at room temperature, wherein the pretreatment solution is a mixed ethanol solution of a coupling agent and phytic acid, the total mass concentration of the coupling agent and phytic acid in the ethanol solution is 1.5-2%, and the mass ratio of the coupling agent to the phytic acid is 10-12:1; (4) The pre-treated Teflon high-temperature cloth is hung up and fully dried, and then soaked in a polyamic acid solution modified by dimethylmethoxychlorosilane grafting at room temperature, hung up to dry, and sintered at high temperature in sections to obtain a Teflon high-temperature cloth after a single dip coating; The preparation of the polyamic acid solution grafted with dimethylmethoxysilyl chloride comprises the following steps: (a) adding anhydrous N,N-dimethylacetamide and 1,3-bis(4'-aminophenoxy)benzene to a reaction kettle, controlling the temperature to 15-20°C, stirring and dissolving, then adding a mixture of pyromellitic dianhydride and hexafluorodianhydride in 3-4 batches, with an interval of 35-40 minutes between each batch. After all the additions are completed, stirring is continued for 10-15 hours. The solid content of the polyamic acid solution is adjusted to 20-22% by adjusting the amount of anhydrous N,N-dimethylacetamide. The reaction is continued until the viscosity of the solution reaches 3000-3500 mPa.s, thereby obtaining an ungrafted polyamic acid solution; The molar ratio of the raw materials is: 10-13 parts of 1,3-bis(4'-aminophenoxy)benzene, 6-8 parts of pyromellitic dianhydride, and 3-4 parts of hexafluorodianhydride; (b) adding dimethylmethoxysilyl chloride to the ungrafted polyamic acid solution obtained in step (a) to carry out a grafting modification reaction, wherein the mass ratio of the polyamic acid solution to the dimethylmethoxysilyl chloride is 100:0.5-0.6, sampling for gas chromatography detection, and stopping the reaction when the conversion rate of the dimethylmethoxysilyl chloride reaches more than 98%, adding anhydrous N,N-dimethylacetamide as a solvent to adjust the solid content to 15-16%, thereby obtaining a polyamic acid solution grafted with dimethylmethoxysilyl chloride; (5) soaking the Teflon high-temperature cloth after the first dip coating in a non-grafted modified polyamic acid solution at room temperature, hanging it to dry, and sintering it at high temperature in sections to obtain the Teflon high-temperature cloth after the second dip coating; (6) The Teflon high-temperature cloth after the second dip coating is immersed in the first mixed emulsion at room temperature, hung to dry, first heated to 260-270 ° C and dried for 2-2.5 minutes, and then sintered at 360-365 ° C for 1.5-2 minutes to obtain the Teflon high-temperature cloth after the third dip coating; the first mixed emulsion is a mixture of PFA emulsion, first PTFE emulsion and water, the mass ratio of PFA emulsion to first PTFE emulsion is 1:0.8-1.2, and the total solid content of the first mixed emulsion is 30-35%; the first PTFE emulsion is JF-4DCD emulsion; (7) The Teflon high-temperature cloth after three dip coatings is immersed in the second mixed emulsion at room temperature, hung to dry, first heated to 260-270 ° C and dried for 2-2.5 minutes, and then sintered at 370-375 ° C for 2.5-3 minutes to obtain the Teflon high-temperature cloth after four dip coatings; the second mixed emulsion is a mixture of the second PTFE emulsion, the third PTFE emulsion and water, the mass ratio of the second PTFE emulsion to the third PTFE emulsion is 1:2-2.5, and the total solid content of the second mixed emulsion is 45-50%; the second PTFE emulsion is JF-4DCF emulsion, and the third PTFE emulsion is JF-4DCT emulsion.
2. The method according to claim 1, characterized in that In step (1), the ultrasonic washing time is 2-3 minutes.
3. The method according to claim 1, characterized in that In step (2), the solvent soaking time is 4-5 minutes; the ethanol soaking time is 30-60 seconds; the alkali solution soaking time is 2-3 minutes; and the acetic acid neutralization time is 10-20 seconds.
4. The method according to claim 1, wherein In step (2), the tap water washing time is 30-60s, and the deionized water washing time is 1-2min; the drying temperature is 130-140°C, and the drying time is 3-4min.
5. The method according to claim 1, wherein In step (3), the pretreatment liquid is immersed for 40-60 seconds; In step (3), the coupling agent is γ-aminopropylmethyldiethoxysilane or 3-aminopropyltrimethoxysilane.
6. The method according to claim 1, characterized in that In step (4), the soaking time is 40-50 seconds; In step (4), the segmented high-temperature sintering includes: 130°C / 10 min, 200°C / 10 min, 320°C / 5 min, and 350°C / 5 min.
7. The method according to claim 1, characterized in that In step (5), the soaking time is 40-50 seconds; In step (5), the segmented high-temperature sintering includes: 150°C / 10 min, 250°C / 10 min, 330°C / 5 min, and 360°C / 5 min.
8. The method according to claim 1, characterized in that In step (5), the preparation of the ungrafted polyamic acid solution comprises the following steps: Add anhydrous N,N-dimethylacetamide and 1,3-bis(4'-aminophenoxy)benzene to a reaction kettle, control the temperature to 15-20° C., stir and dissolve, then add a mixture of pyromellitic dianhydride and hexafluorodianhydride in 3-4 batches, with an interval of 35-40 minutes between each batch. After all the additions are completed, continue stirring for 10-15 hours, adjust the solid content of the polyamic acid solution to 20-22% by adjusting the amount of anhydrous N,N-dimethylacetamide, and continue the reaction until the viscosity of the solution reaches 3000-3500 mPa.s to obtain an ungrafted polyamic acid solution; The molar ratio of the raw materials is: 10-13 parts of 1,3-bis(4'-aminophenoxy)benzene, 6-8 parts of pyromellitic dianhydride, and 3-4 parts of hexafluorodianhydride.
9. The method according to claim 1, characterized in that In step (6) and step (7), the soaking time is independently 30-40 seconds; The PFA emulsion is the model AD-2CRER product of Daikin Corporation of Japan; JF-4DCD emulsion, JF-4DCF emulsion and JF-4DCT emulsion are all products of Juhua Group Co., Ltd.
Citation Information
Patent Citations
Teflon high-temperature coating cloth, preparation method and application thereof
CN110117908A
Soluble polyimides and diimides for spin-on carbon applications
US20220041810A1